Effectiveness of ISO 14001 environmental management systems in enhancing corporate environmental sustainability at Unilever Southeast Africa in Harare, Zimbabwe - Marambanyika, Thomas; Mutekwa, Timothy (Clarion University of Pennyslvania, 2017)
ISO 14001 environmental management system remained one tool widely implemented to mitigate industry's negative impacts on both aquatic and terrestrial life. However, skepticism still surrounds the worthiness of this tool in environmental management, as it merely sets a framework without stringent measures. The paper seeks to explore the effectiveness of the standard at Unilever South East Africa in improving corporate environmental performance and ultimately addressing the goals of sustainable development. Evaluation of the tool was accomplished with the aid of ISO 14031 environmental performance evaluation guidelines. Notwithstanding, the fact that the company has been improving its environmental performance, this in most cases lingered outside permitted legislative limits at the expense of recipient environment. In order for the standard to attain meaningful achievements in the realm of environmental management, there must be harmonization of local authority and central government's environmental regulations and coordination of industrial inspectorate activities to avoid conflicts.